Mapping the Potential of IAIN Ponorogo English Education Students in Facing the Industrial Revolution 4.0 - Nurhidayati, Maulida; Khasanah, Nurul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The industrial revolution is changing the way people live today. Everything can change by technological advances that integrate themselves into people's lives, including in the world of education. Indonesia has made 10 national priorities designed to face the era of the industrial revolution 4.0, including redesigning the educational curriculum to adapt to the 4.0 Industrial era, which utilizes technology in learning. It must indirectly be followed by strengthening the competence of prospective teacher students in designing and developing increasingly meaningful learning. Prospective teacher students must be able to develop abilities in facing the development of the times, including mastery of technology and competence according to Law no. 14 of 2005 and 21st-century abilities. This study aims to describe the knowledge of prospective teacher students about technology-assisted learning media and classify the competencies and abilities of the students. In this study, a quantitative approach was used. The respondents were 71 students of the English Language Education (TBI) IAIN Ponorogo. Data analysis was performed using descriptive statistics and cluster analysis. The results of the study showed that TBI students have begun to get to know several technology-assisted learning media such as Google Classroom, Quizizz, and other interactive learning media. However, there are still many who only know one type of media. The results of competency mapping according to Law no. 14 of 2005 and 21st-century abilities show that many TBI students are still included in the low ability group. These results show that students should make more efforts to improve their abilities and competencies before entering society. Students must begin to be active to improve their mastery of technology-assisted learning media to be able to keep up with the world’s development.